-7.8x-10=5.2-2(4x-8.6)-5x

Simple and best practice solution for -7.8x-10=5.2-2(4x-8.6)-5x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7.8x-10=5.2-2(4x-8.6)-5x equation:



-7.8x-10=5.2-2(4x-8.6)-5x
We move all terms to the left:
-7.8x-10-(5.2-2(4x-8.6)-5x)=0
We calculate terms in parentheses: -(5.2-2(4x-8.6)-5x), so:
5.2-2(4x-8.6)-5x
determiningTheFunctionDomain -2(4x-8.6)-5x+5.2
We add all the numbers together, and all the variables
-5x-2(4x-8.6)+5.2
We multiply parentheses
-5x-8x+17.2+5.2
We add all the numbers together, and all the variables
-13x+22.4
Back to the equation:
-(-13x+22.4)
We get rid of parentheses
-7.8x+13x-22.4-10=0
We add all the numbers together, and all the variables
5.2x-32.4=0
We move all terms containing x to the left, all other terms to the right
5.2x=32.4
x=32.4/5.2
x=6+1/4.3333333333333

See similar equations:

| (8s+5)+77=90 | | 288=4-v | | 144-y=202 | | 4k+22+14=70 | | 34-v=245 | | 163=86-u | | -2x+6=30-6 | | 167=97-y | | 3x-48=6x+18 | | -10y+4y=-7 | | 9-7x+5x=-13 | | |y+4|=18 | | o-7.8=8.5 | | 8(8)=2(k+1) | | 23x+9=8(13x−2) | | 8=|m+2| | | 9g=-12+15g) | | -2=25x+17=-35 | | O.2(-x+1)-1.2=2x-(4x+1) | | 9g=-12+5g) | | 8(8)=2(k+2) | | 5x-8/x-4=0 | | x,5(2x+3)=3(3x+5) | | (3/x(x+3))-(1/x)-(4/(x+3))=0 | | 6x+2(x-1)=18 | | 18-(3p-6)=21-(5p-8) | | 0.4x8=3.2 | | -5(-5+4a)=-23-7a | | 5/2v-3/2=-4v-1/3 | | 4e-5=-11 | | 0,2x-0,5=0,1 | | 1053=-9(10r-7 |

Equations solver categories